2017
DOI: 10.1111/all.13263
|View full text |Cite
|
Sign up to set email alerts
|

Blood and nasal epigenetics correlate with allergic rhinitis symptom development in the environmental exposure unit

Abstract: This study revealed novel and rapid epigenetic changes upon exposure in a controlled allergen challenge facility, and identified baseline epigenetic status as a predictor of symptom severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 43 publications
0
37
1
1
Order By: Relevance
“…Instead some epigenetic modifications must be involved in the onset of AR (Shinohara et al, 2007 , TPSG1, SLFN12 and MUC4 in the peripheral blood mononuclear cells (North et al, 2018), and IL13 in house dust mite-sensitized AR patients (Li et al, 2016). However, this association did not occur with late pregnancy or with paternal AR symptoms, which clearly demonstrated this disease was not solely due to genetic information transferred from the parents.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Instead some epigenetic modifications must be involved in the onset of AR (Shinohara et al, 2007 , TPSG1, SLFN12 and MUC4 in the peripheral blood mononuclear cells (North et al, 2018), and IL13 in house dust mite-sensitized AR patients (Li et al, 2016). However, this association did not occur with late pregnancy or with paternal AR symptoms, which clearly demonstrated this disease was not solely due to genetic information transferred from the parents.…”
Section: Discussionmentioning
confidence: 97%
“…Instead some epigenetic modifications must be involved in the onset of AR (Shinohara et al, 2007 (Nestor et al, 2014). Recently more and more case studies have revealed aberrant methylation status in the promoter regions of AR-related genes, such as IFNG and IL4 in CD4 + T cells of paediatric AR , TPSG1, SLFN12 and MUC4 in the peripheral blood mononuclear cells (North et al, 2018), and IL13 in house dust mite-sensitized AR patients (Li et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins instigate the adverse immune response in sensitized individuals (Figure 3) [128,154,155,156]. In addition, single and repeated exposures to pollen in allergic individuals have been shown to induce epigenetic changes, both in the blood and the nasal tissue [157]. …”
Section: Reviewmentioning
confidence: 99%
“…In addition, changes in mucin 4 (MUC4) DNA methylation in nasal brushings correlate with decrease in peak nasal inspiratory flow. 22 Zhang et al 23 evaluated genome-wide DNA methylation patterns and allergic sensitization during adolescence and found that DNA methylation at cg10159529 is strongly correlated with expression of IL5RA, which is associated with allergic diseases. DNA methylation is considered to be strongly associated with allergic respiratory diseases.…”
mentioning
confidence: 99%